Integration of knowledge as a way forward - Omer, Spahic (IIUMToday, 2019)
Islam is the religion of guidance and truth. It conveys truth to man and teaches him the ways how to grasp, actualize and apply it. Existence and truth are virtually synonymous. Islam thus teaches man how to be true to himself and live life not according to the fluctuating whims and limited capacities of his weak being, but according to the absolute will and infinite knowledge of his Creator and Master. In Islam, man is created as an honourable being. He is accorded the meritorious title of Almighty Allah’s vicegerent, or trustee, on earth. In order to succeed in his challenging tasks, attaining in the process his Creator’s pleasure and happiness in both worlds, man is asked, among other things, to seek knowledge from the cradle to the grave. Such is seen as a key to all goodness. Man is asked to awaken his consciousness and satiate his inherent cognitive capabilities. This is so because man is born to learn and know, just as he is born to submit to the will of his Creator and worship him. Knowledge is seen as the greatest asset, and ignorance as the ultimate liability and hindrance. While knowledge is a twin brother of guidance and truth, ignorance, on the other hand, is a twin brother of falsehood, misguidance and scepticism.